Versatile and robust synthesis process for the fine control of the chemical composition and core-crystallinity of spherical core–shell Au@Ag nanoparticles. (8th December 2020) - Lee, Suyeon; Portalès, Hervé; Walls, Michael; Beaunier, Patricia; Goubet, Nicolas; Tremblay, Benoit; Margueritat, Jérémie; Saviot, Lucien; Courty, Alexa
Abstract: Au nanoparticles (NPs) characterized by distinct surface chemistry (including dodecanethiol or oleylamine as capping agent), different sizes (∼5 and ∼10 nm) and crystallinities (polycrystalline or single crystalline), were chosen as seeds to demonstrate the versatility and robustness of our two-step core–shell Au@Ag NP synthesis process. The central component of this strategy is to solubilize the shell precursor (AgNO3 ) in oleylamine and to induce the growth of the shell on selected seeds under heating. The shell thickness is thus controlled by the temperature, the annealing time, the (shell precursor)/(seed) concentration ratio, seed size and crystallinity. The shell thickness is thus shown to increase with the reactant concentration and to grow faster on polycrystalline seeds. The crystalline structure and chemical composition were characterized by HRTEM, STEM-HAADF, EELS and Raman spectroscopy. The plasmonic response of Au@Ag core–shell NPs as a function of core size and shell thickness was assessed by spectrophotometry and simulated by calculations based on the discrete dipole approximation (DDA) method. Finally, the nearly monodisperse core–shell Au@Ag NPs were shown to form micrometer-scale facetted 3D fcc-ordered superlattices (SLs) after solvent evaporation and deposition on a solid substrate. These SLs are promising candidates for applications as a tunable surface-enhanced Raman scattering platform.